EDUKASI CARA MENGHILANGKAN KONTAMINASI SOIL TRANSMITTED HELMINTHS (STH) PADA SAYUR LALAPAN SEBAGAI UPAYA PEMBERANTASAN KASUS KECACINGAN - Indah Sari (IKesT Muhammadiyah Palembang, 2022)
Indonesia is an agricultural country that has high rainfall, tropical climate, and fertile soil so that it is rich in abundant natural resources and Indonesia's strategic position is one of the countries that has great potential in producing agricultural products such as vegetables. Vegetables are included in staple foods that are rich in nutrients and are widely consumed by the Indonesian people. Indonesian people often use vegetables in the form of fresh vegetables. Lalapan is vegetables that are served raw and usually eaten with rice and other side dishes, such as fried chicken, fried fish, chili sauce and so on. Consuming fresh vegetables is one source of cases of Soil Transmitted Helminth (STH) infection in humans. Soil Transmitted Helminth (STH) infection is often known to the public as worm infection. Worm infections are infectious diseases caused by worm parasites that can endanger health and are described in nutritional status. Worm infections often infect and have a very detrimental impact.